Educational technologies on sexually transmitted infections for incarcerated women - Isaiane da Silva Carvalho; Tatiane Gomes Guedes; Simone Maria Muniz da Silva Bezerra; Fábia Alexandra Pottes Alves; Luciana Pedrosa Leal; Francisca Márcia Pereira Linhares (Universidade de São Paulo, 2020)
Objective: to analyze in the scientific literature the educational technologies on sexually transmitted infections used in health education for incarcerated women. Method: an integrative review carried out by searching for articles in the following databases: Scopus, Cumulative Index of Nursing and Allied Health, Education Resources Information Center, PsycInFO, Medical Literature Analysis and Retrieval System Online, Latin American Literature in Health Sciences, Cochrane, and the ScienceDirect electronic library. There were no language and time restrictions. A search strategy was developed in PubMed and later adapted to the other databases. Results: a total of 823 studies were initially identified and, after applying inclusion and exclusion criteria, eight articles were selected. Most of them were developed in the United States with a predominance of randomized clinical trials. The technologies identified were of the printed materials type, isolated or associated to simulators of genital organs, videos, and games. Conclusion: the technologies on sexually transmitted infections used in health education for incarcerated women may contribute to adherence to the prevention of this serious public health problem in the context of deprivation of liberty.